Optimization design for vibration reduction of complex configuration structures via global reduced-order basis. Issue 10 (3rd October 2021) - Li, Yuwei; Tian, Kuo; Hao, Peng; Wang, Bo
Abstract : Despite numerous studies on vibration reduction techniques for mechanical systems, the expensive computational cost is still a challenging issue for complex structures with a huge number of degrees of freedom. A constructing method of global reduced-order basis (ROB) is proposed in this article by combining proper orthogonal decomposition (POD) with an iterative process. The POD method is adopted to extract the principal component of the snapshot matrix, which collects mode shapes of representative configurations. The objective of the iterative process is to find the global ROB with enough prediction accuracy in the entire design space. Once the global ROB has been constructed, the optimization design for vibration reduction is performed by reduced-order models. Finally, the effectiveness and efficiency of the proposed method are verified through an example of an S-shape stiffened curved shell. The proposed global ROB obtains similar optimal results to the mode-superposition method, with 33.51% computational cost saving.